Biomechanical simulation of healing process of fractured femoral shaft applied by composite intramedullary nails according to fracture configuration. (1st February 2018) - Mehboob, Ali; Chang, Seung-Hwan
Abstract: Flexible composite implants are receiving increased attention in this modern era of orthopedics for the stabilization of long bone fractures because they facilitate tissue development in calluses. An endochondral ossification process involves generation of calluses, and it is well known that this significantly affects the stabilization and healing of the broken bones. Therefore, the exact configuration of callus formation is highly important for the accurate simulation of bone healing. In this study, finite element analysis was performed to estimate the external callus shape by using the rejection coefficient (RC) algorithm. Regarding the application of a fractured femur by an intramedullary (IM) nail, the bone healing simulation was conducted by employing the biphasic mechano-regulation algorithm according to the fracture type (transverse (0°) and oblique (35°)), fracture location (proximal, medial, and distal ends), and nail property. The simulation results revealed that a glass/polypropylene fabric composite (Twintex [0]2nT ) IM nail, which has the similar Young's modulus to the cortical bone, provided the most appropriate bio-mechanical environment for bone healing.